2010
DOI: 10.1038/jhh.2010.68
|View full text |Cite
|
Sign up to set email alerts
|

Meta-based association of the lipoprotein lipase gene S447X variant with hypertension and blood pressure variation

Abstract: Association of the lipoprotein lipase (LPL) gene S447X variant with hypertension has been investigated extensively, whereas the results are often irreproducible. We therefore conducted a meta-analysis to examine whether S447X variant was associated with hypertension and blood pressure variation. Case-control reports published in English language and humans were identified from MEDLINE, EMBASE and Web of Science search engines as of 10 December 2009. Fixed-effects model was applied to pool data in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…The mutated allele has also been associated with lower TG and SBP levels as well as higher HDL-C levels [ 33 ]. Consistent with such results, the presence of the p.474X allele has shown in previous reports a lower risk for developing coronary heart disease [ 33 ] and hypertension (OR 0.78; 95% CI: 0.62–0.98, P = 0.03) [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…The mutated allele has also been associated with lower TG and SBP levels as well as higher HDL-C levels [ 33 ]. Consistent with such results, the presence of the p.474X allele has shown in previous reports a lower risk for developing coronary heart disease [ 33 ] and hypertension (OR 0.78; 95% CI: 0.62–0.98, P = 0.03) [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…But, in a large cohort of white subjects, the LPL Asp9Asn mutation, LPL T-93G promoter mutation, and LPL Asn291Ser mutation were not associated with an increased risk for PE [186]. Moreover, despite the fact that a recently published meta-analysis showed that subjects carrying the 447X variant have a lower risk of primary hypertension (OR 0.79; 95% CI 0.64-0.98; p = 0.03), the same SNP was significantly associated neither with hypertension nor with BP variation during pregnancy [187].…”
Section: Genes Involved In Lipid Metabolism and Oxidative Stresscontrasting
confidence: 60%
“…Higher HDL-C and lower TG levels or a decreased risk for cardiovascular diseases in carriers of the Ser447Stop variant have been observed [23,24]. There are studies showing an association between this variant and preeclampsia [25,26]. Studies conducted by Wittrup et al [27]and Kim et al [16], but not Zhang et al [28] suggest a higher risk for cerebrovascular disease and preeclampsia in association with the Asn291Ser variant.…”
Section: Discussionmentioning
confidence: 88%